Penerapan Peran Media Relations Dalam Meningkatkan Citra Universitas Muhammadiyah Jakarta - Amelia, Cindy; Rahma , Dwi; Shalsabilla, Apriliani Putri; Patrianti , Tria (Telangke:Jurnal Telangke Ilmu Komunikasi, 2024)
One of the main activities of Public Relations itself is media relations. Media relations, or relations with mass media, is a strategic means for universities to improve the image of UMJ. Media relations allows the University of Muhammadiyah Jakarta to build public awareness about their programs, activities, and achievements. Through publications in mass media and online media, they can reach a wider audience and introduce the University of Muhammadiyah Jakarta to the public. This study aims to understand and analyze in depth the application of media relations in improving the image of the University of Muhammadiyah Jakarta. The image of the university is one of the things that is quite important in attracting prospective students, supporting development efforts carried out by university residents in terms of research and publications, and strengthening cooperation networks with existing stakeholders. Furthermore, interviews will be conducted with public relations staff of the University of Muhammadiyah Jakarta regarding public relations work practices through existing Media Relations. As a result, media relations has a very significant role in improving the image of an institution, especially in the context of today's digital era. Digital transformation has brought major changes in various aspects of life, including education. With registration, payments, and online classes all going digital, the existence of an institution without a digital presence can make it lag far behind the competition.